The Use of Erythropoietin and its Derivatives to Treat Spinal Cord Injury - Mofidi, A.; Bader, A.; Pavlica, S. (Mini Reviews in Medicinal Chemistry, 2011)
Spinal Cord Injury (SCI) is a complex process which leads to destruction of neuronal tissue and also vascular structure. After SCI many potentially toxic substances are activated and released into the injury site causing secondary degeneration. Erythropoietin (EPO) is a possible therapeutic strategy to treat SCI. Over the last decade attention has been focused on the molecular mechanisms underlying its neuroprotective effects. A major concern expressed by clinicians is that besides its protective effects, EPO also demonstrates hematopoietic activity and increases the risk for thrombosis after the systemic administration of multiple doses of this glycoprotein. Recently, tissue protective functions of EPO have been separated from its hematopoietic actions leading to the development of EPO derivatives and mimetics. Neuroscientists are focusing on recombinant human EPO (rhEPO) and its non-erythropoietic derivatives, investigating their anti-apoptotic potential and anti-inflammatory function as well as their role in restoring vascular integrity. Carbamylated erythropoietin (CEPO) and asialo erythropoietin (AsialoEPO) are structural derivatives of EPO that have no effect on erythrocyte mass whereas they retain its neuroprotective effects. In this review article, we provide a short overview of the animal studies on rhEPO and its derivatives in experimental models of SCI. Both the efficacy and the safety profile of EPO-structural and functional variants are still to be demonstrated in patients. Further clinical studies should reveal whether derivatives and variants of erythropoietin provide any benefits over the use of rhEPO in the treatment of spinal cord injury observed in the experimental studies.
Keywords: EPO-derivatives